SAINT OF SOUTH KALIMANTAN: BANJAR PEOPLE - Umilati, Dhea; Iqbal, Muhammad; Husni, Muhammad; Anggraeni, Nur Najmi; Romdhoni, Alfi Rohmatur (IAIN Palangka Raya, 2023)
The grave of Muhammad Nafis is considered sacred by the Banjar people. As a Banjar Sufi scholar who is known as a figure who contributed to the spread of Islam in Banjar, this tomb is often visited by the community for pilgrimage. This paper aims to investigate the motives for the pilgrimage to Muhammad Nafis' grave. As a complement to several previous studies that have reviewed the life history, works left behind, and the concept of Sufism taught.